Single-cell profiling to transform immunotherapy usage and target discovery in immune-mediated inflammatory diseases - Chapelle, Nicolas; Fantou, Aurelie; Marron, Thomas; Kenigsberg, Ephraim; Merad, Miriam; Martin, Jerome C. (Frontiers in Immunology, 2022)
Immunotherapy drugs are transforming the clinical care landscape leading to a surge for the identification of novel immune targets of major human diseases from cancer, to inflammatory diseases, cardiovascular diseases, neurodegenerative diseases and even aging. Yet most FDA-approved drugs target known pathophysiological pathways for which medicine are already available. This reflects a common struggle to identify novel and relevant molecular drivers of disease that stems from a suboptimal understanding of human disease pathophysiology and crisp knowledge of target expression profile during disease course. Here we discuss the potential for single-cell technologies to reveal relevant pathogenic cellular programs in human diseases and to enhance drug development strategies and clinical trial design.